The Implementation of Student Team Achievement Division (STAD) Technique in Teaching Vocabulary of Descriptive Text to The Seventh Grade Students of SMP Negeri 1 Kamal - Moh. Arief Wahyudi (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2017)
Vocabulary is the main language element which has to be learned since it is the first thing which is introduced in learning English. In learning vocabulary of descriptive text, the teacher has to make an enjoyable learning so that the students will not feel bored on the lesson. One way in making an enjoyable learning is by implementing cooperative learning because the students can interact with their friends in doing their jobs. Here, the type of cooperative learning which is used in this study is Student Team Achievement Division (STAD). The subject of the study was the students of 7A. The research used some instruments in collecting the data such as; observation checklist which was used to get the data about the implementation of STAD technique in teaching descriptive text and questionnaire was used to know the students’ responses toward the implementation of STAD technique. After doing some observations and analyzing the data, the writer found some findings. The first finding is about the implementation of STAD technique. The implementation of STAD technique was not in line with the theory of STAD technique. The teacher did not implement five major components of STAD technique. She just implemented three major components; class presentation, teams, quizzes. The second finding is about the students’ responses toward the implementation of STAD technique. Almost all of students liked the technique which was used by the teacher since they could improve their sense of unity, responsibility, and self-confidence by helping each other in their group. They could also solve their task or job easily when they worked in a group. In conclusion, STAD technique has not been succeeded implemented in teaching descriptive text to the Seventh Graders of SMP Negeri 1 Kamal, since the teacher did not understand the STAD technique in depth